Natural and hybrid lighting effects on architecture students' creativity: a case study in Mostaganem - Derouiche, Zineb; Kacemi, Malika; Benameur, Okba (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
Lighting is a critical factor influencing creativity and productivity in educational environments, particularly for architecture students, whose work demands both technical precision and imaginative exploration. This study investigates the impact of architectural design and lighting conditions on creativity within eight drawing workshops at the Department of Architecture, Mostaganem, Algeria. The methodology combined architectural surveys to document spatial characteristics, photometric measurements to objectively assess natural and hybrid lighting quality, and the Torrance Test of Creative Thinking (TTCT) to evaluate students’ creative performance. Findings revealed significant disparities in lighting conditions across the workshops, with Workshop 2 exhibiting optimal illumination and Workshop 4 demonstrating critically insufficient levels. Improved lighting conditions were shown to significantly enhance creativity in geometric tasks, particularly in fluency, flexibility, originality, and elaboration. However, for figural tasks requiring complex representational skills, lighting improvements alone had a limited effect, suggesting that higher-order creative processes depend on additional cognitive and instructional support. The study concludes that well-designed lighting is essential for fostering creativity in precision-based tasks, while more holistic approaches integrating environmental and pedagogical enhancements are necessary for advanced creative outcomes. These findings provide actionable insights for optimising educational spaces to support the cognitive and creative demands of architecture students.